Creating newsletters, brochures, and pamphlets : a how-to-do-it manual - Blake, Barbara Radke; Stein, Barbara L. (New York : Neal-Schuman Publishers, 1992)
Ideas and techniques for librarians to produce a newsletter with chapters on budgets, designs, writing, editing, typewriter skills and desktop publishing, layout and paste up, and mailings.
Includes bibliographical references (p. 85-86) and index.
Wilson's Junior High School.
Wilson's Public Library.
Wilson's Senior High School.
Professional
Keywords: Advertising -- Libraries -- Handbooks, manuals, etc; Libraries -- Publishing -- Handbooks, manuals, etc; Newsletters -- Publishing -- Handbooks, manuals, etc; Pamphlets -- Publishing -- Handbooks, manuals, etc; Public relations -- Libraries -- Handbooks, manuals, etc; Advertising -- Libraries -- Handbooks, manuals, etc; Libraries -- Public relations -- Handbooks, manuals, etc